The physical characteristics of cheese made of milk, colostrum and both during the ripening - Astuti, F. D.; Setyawardani, T.; Santosa, S. S. (Diponegoro University, 2021)
This study aimed to understand the physical characteristics of cheese made of cow milk, colostrum, and milk+colostrum ripened for 20 days. Two factors in this study were cheese made of three materials: A (100% cow milk), B (50% cow milk + 50% colostrum) and C (100% colostrum), and ripening time, i.e. 0, 10, and 20 days. The process of cheese production started by heating the raw material, followed by decreasing the temperature, incorporating kefir as the starter. The next step was and the rennet and re-incubate the mixture for one hour until the fluid became solid granules, then the granules were filtered and pressed. The cheese was stored at a low temperature (4-8oC) according to each treatment. Each combination was repeated three times. The physical properties of cheese examined in this study were color, texture, pH, and microstructure. The result showed that the raw materials of cheese would produce different cheese colours in terms of lightness (L*), yellowness (b*), and whiteness index (WI) as well as cheese texture (hardness and gumminess). Also, ripening time would affect the hardness, springiness gumminess, chewiness, L*, a*, and WI of cheese. Colostrum added in cheesemaking has increased both yellowness and cavities in the microstructure.